Pancreatic Steatosis Is Not Associated With Exocrine Pancreatic Function in Overweight Type 2 Diabetes Patients. Issue 9 (October 2017) - Vendrik, Karuna E.W.; Tonneijck, Lennart; Muskiet, Marcel H.A.; Kramer, Mark H.H.; Pouwels, Petra J.W.; Pieters-van den Bos, Indra C.; Diamant, Michaela; Cahen, Djuna L.; van Raalte, Daniël H.; Smits, Mark M.
Abstract : Supplemental digital content is available in the text.